MATEC Web of Conferences - Tsibulskii (Tsibulskiy) specialist in the field of power engineering Assistant of Tomsk Polytechnic University; Galashov specialist in the field of power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences; Melnikov specialist in the field of heat and power engineering assistant of Tomsk Polytechnic University; Kiselev Specialist in the field of electrical engineering Assistant of the Department of Tomsk Polytechnic University, Candidate of technical sciences; Bannova Specialist in the field of heat and power engineering Engineer of Tomsk Polytechnic University (EDP Sciences, 2018)
The results of analysis of the literature on the calculation of the heat transfer coefficient of an air condenser in the flow past a bundle of finned tubes by an air flow. The methods of calculation are disassembled, marked advantages and disadvantages of each. Calculations of the heat transfer coefficient for each method are given; the results compared with the experimental data.